2013
DOI: 10.1371/journal.pone.0063713
|View full text |Cite
|
Sign up to set email alerts
|

A Universal Pedicle Screw and V-Rod System for Lumbar Isthmic Spondylolysis: A Retrospective Analysis of 21 Cases

Abstract: ObjectiveTo investigate the surgical outcome of a universal pedicle screw-V rod system and isthmic bone grafting for isthmic spondylolysis.MethodsTwenty-four patients with isthmic spondylolysis at L5 and grade 0–I spondylolisthesis (Meyerding classification) received isthmic bone graft and stabilization using the universal pedicle screw-V rod system. Back pain was evaluated using the visual analog scale (VAS) and time to bone healing, improvement in spondylolisthesis and intervertebral space height at L5/S1 an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
12
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(13 citation statements)
references
References 18 publications
1
12
0
Order By: Relevance
“…There was a hypothesis from this study that the pedicle screw fixation did not harm to the index disc and the adjacent disc. This hypothesis was similar to the reporting of Chen et al The pedicle screw‐V rod system directly repairs the isthmus of the vertebra and the procedure does not impact on adjacentvertebral segments and causes no injury to the diseased intervertebral disc 9 . Furthermore, the Quadrant retractor can provide good illumination, a good visual field and minimal damage to the surrounding tissues, resulting in a faster recovery and pain relief postoperatively.…”
Section: Discussionsupporting
confidence: 88%
See 3 more Smart Citations
“…There was a hypothesis from this study that the pedicle screw fixation did not harm to the index disc and the adjacent disc. This hypothesis was similar to the reporting of Chen et al The pedicle screw‐V rod system directly repairs the isthmus of the vertebra and the procedure does not impact on adjacentvertebral segments and causes no injury to the diseased intervertebral disc 9 . Furthermore, the Quadrant retractor can provide good illumination, a good visual field and minimal damage to the surrounding tissues, resulting in a faster recovery and pain relief postoperatively.…”
Section: Discussionsupporting
confidence: 88%
“…Chen et al . reported that pedicle screw fixation using the pedicle screw and V‐rod system successfully fused the fracture sites of the pars interarticularis in all 21 patients in their study and that the average VAS scores for LBP decreased from 7.5 (5–9) preoperatively to 3.04 (2–5) postoperatively and 1.43 (0–3) 6 months postoperatively 9 . A retrospective study of the screw hook system for pedicle fixation by Debusscher and Troussel showed that approximately 91% of patients achieved good fusion results and that the VAS scores for LBP decreased from an average of 7.75 preoperatively to 1.7 at the 4‐year follow‐up 10 .…”
Section: Discussionmentioning
confidence: 86%
See 2 more Smart Citations
“…According to the literature, there is a slight preference for percutaneous PS techniques versus open and minimally-open techniques due to reduced operative time, blood loss, and incision length as well as the optimal positioning of the screws with this procedure (6). The percutaneous placement of PS in the lumbar spine for various conditions, such as pars interarticularis defects (7), traumatic or osteoporotic vertebral fractures (8)(9)(10)(11), restoration and/or preservation of lumbar lordosis during correction procedures for severe kyphoscoliosis (12,13), spondylolysis (14)(15)(16), spondylolisthesis (17,18), and finally to provide supplemental stabilization for lumbar interbody fusion procedures (19)(20)(21)(22). Another relatively new indication for percutaneous PS placement is in obese patients with spinal deformities and severe degenerative lumbar disease as it reduces the operative site exposure, surgical time, and hospitalization and decreases the postoperative infection rate (23)(24)(25).…”
Section: Introductionmentioning
confidence: 99%